Hubungan antara Kemandirian Belajar dengan Konsep Diri Siswa Pengguna Jejaring Sosial Facebook - Nisa, Khoirun; Setyowani, Ninik (Indonesian Journal of Guidance and Counseling: Theory and Application, 2016)
This research is based on the data collected from Praktik Pengalaman Lapangan (PPL) on 8th grade students of SMP Negeri 7 Semarang that shows that many students still have low consciousness of independent learning and negative self-concept. The aim of this research is to find out relationship between independent learning and self-concept illustration of students using facebook. This research used ex post facto with correlational quantitative method. The populations used in this research are students of SMP Negeri 7 Semarang who use facebook. Data-collection method uses psychology scale which is independent learning and self-concept scale. Data-analysis technique uses percentage descriptive statistics and correlation analysis product moment. The result of percentage descriptive statistics showed that studentsâ independent learning was on high category (74.8 %) and studentsâ self-concept was on high category (77.8 %). According to the result of correlation product moment test, it showed that rhitung = 0,619 > rtabel = 0,148 that means Ha is accepted and Ho is rejected. The result indicates there is positive and significant relationship between independent learning and self-concept of students of SMP Negeri 7 Semarang who use facebook